2006
DOI: 10.1038/sj.cr.7310026
|View full text |Cite|
|
Sign up to set email alerts
|

Local signals in stem cell-based bone marrow regeneration

Abstract: The cellular basis of bone marrow (BM) tissue development and regeneration is mediated through hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs). Local interplays between hematopoietic cells and BM stromal cells (BMSCs) determine the reconstitution of hematopoiesis after myelosuppression. Here we review the BM local signals in control of BM regeneration after insults. Hematopoietic growth factors (HGFs) and cytokines produced by BMSCs are primary factors in regulation of BM hematopoiesis. Morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 47 publications
0
35
0
2
Order By: Relevance
“…Many members of this signaling pathway were upregulated in kidney SP cells, and ISH on adult kidneys again revealed that the members of this pathway were expressed principally in proximal tubules. Notch signaling also has been implicated in specification of podocytes and proximal tubules in the developing kidney (39,40) as well as organ regeneration in bone marrow (41), muscle (42), skin (43), heart (44), and liver (45). The kidney has substantial inherent ability to recover from many types of acute damage, and the involvement of Notch signaling in this process warrants investigation with the caveat that this pathway is highly expressed by the kidney SP, a potential progenitor population.…”
Section: Discussionmentioning
confidence: 99%
“…Many members of this signaling pathway were upregulated in kidney SP cells, and ISH on adult kidneys again revealed that the members of this pathway were expressed principally in proximal tubules. Notch signaling also has been implicated in specification of podocytes and proximal tubules in the developing kidney (39,40) as well as organ regeneration in bone marrow (41), muscle (42), skin (43), heart (44), and liver (45). The kidney has substantial inherent ability to recover from many types of acute damage, and the involvement of Notch signaling in this process warrants investigation with the caveat that this pathway is highly expressed by the kidney SP, a potential progenitor population.…”
Section: Discussionmentioning
confidence: 99%
“…The process of hematopoiesis is tightly regulated by several positive and negative signals. 1,2 Of the different types of blood cells, leukocytes are especially susceptible to intercalating agents, and because of their proliferative activity and constant turnover, they have a rather limited life span. They must constantly be replenished from hematopoietic cells, and because therapeutic cytotoxins attack these cells directly, the BM is very highly sensitive to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these cell types have received much attention, namely HSCs and MSCs. Bone marrow derived MSCs are known for their ability to self-renew, undergo clonal expansion, differentiate into multiple musculoskeletal tissues (such as osteoblasts, chondrocytes, myocytes, marrow stromal cells, tendon-ligament fibroblasts, and adipocytes), support hematopoietic stem cells (HSCs), and regulate the immune system in response to various local cellular, tissue, injury or disease signaling cues and pathways [14][15][16][17][18][19][20][21]. Adult stem cells make up only a small percentage of cells in a tissue and are surrounded by mature cells that have reached the end of the differentiation process and do not have the capacity to proliferate or differentiate [22].…”
Section: Introductionmentioning
confidence: 99%